EffECT OF OCCUPATIONAL SAFETY AND HEALTH TO THE EMPLOYEE PERFORMANCE Of JOB SATISFACTION AS AN INTERVENING VARIABLE (Study at PT. PLN(Persero) Cabang Area Pontianak Bagian Distribusi Jaringan) - B31111065, SYARIFAH MARIANI (Jurnal Manajemen Update, 2016)
The purpose of this study was to determine the influence of health and safety on job satisfaction and performance of employees at PT. PLN (Persero) branch Pontianak area parts distribution network. The population number as many as 34 people. Technique sampling cencus method, because all the population made in the sample. Data was collected by distributing questionnaires to 34 respondents. Data analysis was performed using a model of path analysis (path analysis). The hypothesis in this study proved by using statistical tests. Based on the results of research conducted found that the occupational safety and health a significant effect on job satisfaction at 0.565. Occupational safety and health significantly affect the performance of 0.416. Job satisfaction significantly influence the performance of employees is 0.516. Safety and health to employee performance through employee satisfaction at 0.291. Keywords : Safety, health, Performance of Employees, Job Satisfaction